2020
DOI: 10.1021/acs.macromol.0c00970
|View full text |Cite
|
Sign up to set email alerts
|

Immiscibility of Chemically Alike Amorphous Polymers: Phase Separation of Poly(2-ethyl-2-oxazoline) and Poly(2-n-propyl-2-oxazoline)

Abstract: In biomedicine, polymer blends are frequently applied in wound dressing design or drug delivery. Within these applications, poly­(2-alkyl/aryl-2-oxazoline)­s (PAOx) are emerging as a popular matrix due to excellent biocompatibility and miscibility with other polymers. However, as much is known of PAOx miscibility with other biocompatible polymer systems, so little is known of the miscibility within the PAOx class. We show the remarkable phase separation of two important, structurally alike, amorphous PAOx, i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…This finding is particularly interesting as Hoogenboom recently reported that pEtOx and pPrOx homopolymers show immiscibility when the molar mass exceeded 10 kg/mol (i.e. DP ≈ 100) [68]. One might have expected that pEtOx and pPrOzi would be less miscible than pEtOx and pPrOx, but in the present case we have block copolymers at hand, while Hoogenboom and co-workers studied homopolymer blends, which can be expected to phase separate more readily.…”
Section: Synthesis Characterization and Rheologymentioning
confidence: 59%
“…This finding is particularly interesting as Hoogenboom recently reported that pEtOx and pPrOx homopolymers show immiscibility when the molar mass exceeded 10 kg/mol (i.e. DP ≈ 100) [68]. One might have expected that pEtOx and pPrOzi would be less miscible than pEtOx and pPrOx, but in the present case we have block copolymers at hand, while Hoogenboom and co-workers studied homopolymer blends, which can be expected to phase separate more readily.…”
Section: Synthesis Characterization and Rheologymentioning
confidence: 59%
“…In contrast, the DSC thermogram of pPrOzi 100 - b -pEtOx 100 showed only a single T g at ≈ 26 °C (slightly higher in comparison to pPrOzi 50 - b -pEtOx 50 T g ≈ 23 °C) suggesting that again no microphase separation ( Figure 2 b) occurred in the solid. This finding is particularly interesting as Hoogenboom recently reported that pEtOx and pPrOx homopolymers show immiscibility when the molar mass exceeded 10 kg/mol (i.e., DP ≈ 100) [ 68 ]. One might have expected that pEtOx and pPrOzi would be less miscible than pEtOx and pPrOx, but in the present case we have block copolymers at hand, while Hoogenboom and co-workers studied homopolymer blends, which can be expected to phase separate more readily.…”
Section: Resultsmentioning
confidence: 92%
“…Due to the low T g of P n PrOx and its T CP , the nanofibrous structure is not significantly altered upon contact with water at room temperature. [ 49,52 ]…”
Section: Resultsmentioning
confidence: 99%